Bacterial-Derived Outer Membrane Vesicles are Potent Adjuvants that Drive Humoral and Cellular Immune Responses - J. Timothy Prior; Christopher Davitt; Jonathan Kurtz; Patrick Gellings; James B. McLachlan; Lisa A. Morici (MDPI AG, 2021)
Discovery and development of novel adjuvants that can improve existing or next generation vaccine platforms have received considerable interest in recent years. In particular, adjuvants that can elicit both humoral and cellular immune responses would be particularly advantageous because the majority of licensed vaccines are formulated with aluminum hydroxide (alum) which predominantly promotes antibodies. We previously demonstrated that bacterial-derived outer membrane vesicles (OMV) possess inherent adjuvanticity and drive antigen-specific antibody and cellular immune responses to OMV components. Here, we investigated the ability of OMVs to stimulate innate and adaptive immunity and to function as a stand-alone adjuvant. We show that OMVs are more potent than heat-inactivated and live-attenuated bacteria in driving dendritic cell activation in vitro and in vivo. Mice immunized with OMVs admixed with heterologous peptides generated peptide-specific CD4 and CD8 T cells responses. Notably, OMV adjuvant induced much greater antibody and B cell responses to co-delivered ovalbumin compared to the responses elicited by the adjuvants alum and CpG DNA. Additionally, pre-existing antibodies raised against the OMVs did not impair OMV adjuvanticity upon repeat immunization. These results indicate that vaccines adjuvanted with OMVs elicit robust cellular and humoral immune responses, supporting further development of OMV adjuvant for use in next-generation vaccines.